Description of Mother’s Knowledge and Adherence to Use of Helminthic Drugs in Kuwaluhan Village, Magelang Regency, Central Java - Amanda, Shalma Risqi; Haresmita, Perdana Priya; Wardani, Arief Kusuma; Hadi, Ismanurrahman (Jurnal Ilmu Kesehatan, 2023)
Worm infection has become public health issue with the highest prevalence in children under the age of five and elementary school-aged children. The children have difficulty maintaining the hygienist, especially when they are playing. This study aims to describe the level of knowledge and mothers’ adherence to the use of helminthic drugs in Kuwaluhan Village, Magelang Regency. This research used a descriptive study with both a survey method and a cross-sectional approach. The purposive sampling technique was used, while the questionnaire was distributed to mothers with children under the age of five and elementary school-age children in Kuwaluhan Village RW 2, Magelang Regency, in December 2022. The results showed that the level of knowledge of mothers in Kuwaluhan Village RW 2, Magelang Regency, regarding the use of helminthic drugs out of a total of 74 mothers indicated that 33 respondents (44.59%) had good knowledge, 29 respondents (39.19%) had sufficient knowledge, and as many as 12 respondents (16.22%) had less knowledge. Meanwhile, at the adherence level, respondents were categorized as having high adherence by 1 respondent (1.35%), medium adherence by 73 respondents (98.65%), and low adherence by 0 respondents (0%). Based on these results, most of the mothers in Kuwaluhan RW 2, Magelang Regency have good knowledge and have a medium level of adherence to using helminthic drugs for children.